Dynamic Wireless Power Transfer in Electric Vehicles. Issue 1 (April 2021) - Kumar, Sujit; Paliwal, Himani; Vyas, Shripati; Sekhor, Sasanka; Dave, Vikramaditya; Rao, Srawan Singh
Abstract: An Electrical vehicle can utilize a force move framework to charge the on-board Rechargeable Energy Storage System (RESS the battery) or to give the capacity to the electric engine. It is additionally conceivable to utilize remote force move to charge the batteries while fixed, using charging pads. Both of these arrangements are satisfactory for assessing at home or in-vehicle parking, yet at the same time, require the vehicle to stop in a proper area to charge the battery. We propose an eco-friendly wireless charging system for electric vehicles, which enables wireless charging of the vehicle while running on the highways. The proposed approach is also used for the charging of cars in the shopping malls and other parking places. Moreover, the proposed charging system may require electrical energy from the solar PV systems and wind turbines, installed along the highways. The solar PV system and wind turbines are connected to form a Microgrid system and feed generated electrical energy to the wireless charging system. The surplus electrical energy may be either fed back to the primary grid or used for highway illumination. The wireless charging system also consists of an air-core transformer with its primary winding below the highway surface and secondary mounted on the vehicle. The ac power from secondary passes through a rectifier and dc-dc conversion stage to produce suitable dc voltage and current for the charging of the battery unit.